Sodium ion positive electrode material and preparation method and application thereof

In the preparation of the positive electrode material of sodium ion battery, Fe3(PO4)2 mesophase is prepared using a ball mill for phosphate compound and sintered with pyrophosphate and carbon sources, the problem of inert sodium phosphate-type sodium phosphate is solved. A cathode material with high purity and excellent electrochemical properties simplifies the process and reduces contamination.

CN119503751APending Publication Date: 2025-02-25HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411497057.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials are prone to generate inert sodium phosphate sodium phosphate during the preparation process, resulting in insufficient electrochemical activity, complex process, and pollutant gas emissions.

Method used

The Fe3(PO4)2 mesophase is prepared by ball milling and calcined, and then mixed with pyrophosphate and carbon source to synthesize the pure phase sodium ferric pyrophosphate positive electrode material through high-temperature solid phase reaction, simplifying the process and reducing miscellaneous Generate in proportion.

Benefits of technology

It improves the purity and electrochemical performance of composite sodium ferric pyrophosphate positive electrode material, reduces manufacturing costs and environmental pollution, and is suitable for sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503751A_ABST
    Figure CN119503751A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion positive electrode material as well as a preparation method and application thereof, and relates to the technical field of sodium ion batteries. The preparation method of the sodium ion positive electrode material comprises the following steps: S1, carrying out ball milling on a ferrophosphorus compound, and calcining to obtain an intermediate phase; and S2, mixing the intermediate phase with pyrophosphate, a carbon source and a solvent, drying, sintering, and crushing to obtain a sodium ion positive electrode material, namely the ferric sodium pyrophosphate composite material. The preparation method of the sodium ion positive electrode material is beneficial to inhibition of enrichment of iron element, reduction of local iron-phosphorus ratio and inhibition of generation of electrochemical inert phase sodium ferric phosphate; the preparation method has extremely high atom economy, and solves the problems of environmental protection, safety, cost and the like in preparation of the sodium ion battery positive electrode material ferric sodium pyrophosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are not easily "choked" by foreign countries due to their abundant upstream sodium resources. At the same time, sodium-ion batteries themselves have become one of the more popular tracks in the new energy field in the past two years due to their advantages such as low cost, high safety, and good low-temperature performance. In the future, they are expected to replace lead-acid batteries and squeeze some of the space for lithium iron phosphate batteries. Sodium-ion batteries have broad prospects and a promising future.

[0003] Among the developed sodium-ion battery cathodes, polyanionic compounds have great commercial prospects due to their good ion diffusion channels, high safety, and superior structural stability determined by their unique structural framework. For iron-based phosphate systems, the most likely commercialization is the sodium iron phosphate pyrophosphate composite system, which is similar to lithium iron phosphate and can be formed by high-temperature solid-phase sintering, so its manufacturing cost is low. However, when this material system is synthesized according to the dosage ratio, there will always be more or less impurities of sodium iron phosphate, so how to obtain a pure composite sodium iron phosphate pyrophosphate phase is the main problem in improving the application of this material.

[0004] At present, in the existing preparation method of sodium ferric pyrophosphate, when soluble ferrous sulfate, ferrous nitrate, and ferrous chloride are used, NO is generated during the spray drying or sintering process. x 、SO x , Cl2 and other polluting or toxic gases, causing great pollution to the environment; when FeC2O4, Fe2O3, and FePO4 are used as iron sources, ball milling or sand milling is usually required for mixing. During the mixing process, it is difficult for the three components of Na, Fe, and P to achieve uniform mixing at the atomic level. The crystal form of sodium ferric phosphate pyrophosphate is closely related to the iron-phosphorus ratio in the local area. When the local iron content is high, inert sodium ferric phosphate ore type sodium ferric phosphate will be generated. Since sodium ferric phosphate ore type sodium ferric phosphate is not electrochemically active, it cannot be used as a positive active material for sodium ion batteries, which will have an adverse effect on its electrochemical properties. Therefore, it is imperative to develop an advanced synthetic route to prepare the phase of pure composite sodium ferric phosphate pyrophosphate, and to combine structural optimization and interface design to improve the performance of the material. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a sodium ion positive electrode material and its preparation method and application. The present invention provides a high atom economy synthesis method of sodium electropolyanion positive electrode material, aiming to improve the purity of composite phosphate sodium iron pyrophosphate and reduce the generation of impurities; at the same time, simplify the synthesis process of the material, reduce the synthesis difficulty and manufacturing cost of the material.

[0006] The present invention provides a method for preparing a sodium ion positive electrode material, comprising the following steps:

[0007] S1, calcining the ferrophosphorus compound after ball milling to obtain an intermediate phase;

[0008] S2. The intermediate phase is mixed with pyrophosphate, a carbon source, and a solvent, dried, sintered, and crushed to obtain a sodium ion positive electrode material, namely, a sodium iron phosphate pyrophosphate composite material.

[0009] In the present invention, iron ions and phosphate ions are reacted at high temperature solid phase to synthesize a uniform Fe3(PO4)2 intermediate phase based on the chemical equation 2Fe3P2+16CO2→2Fe3(PO4)2+16CO, thereby avoiding the enrichment of local iron elements. Then, pure phase sodium ferric phosphate pyrophosphate is synthesized based on the chemical equation Fe3(PO4)2+Na4P2O7+C→Na4Fe3(PO4)2P2O7 / C. The composite sodium ferric phosphate pyrophosphate polyanion-type positive electrode material obtained by the preparation process of the present invention exhibits excellent electrochemical comprehensive performance and is suitable for sodium ion batteries.

[0010] Preferably, in S1, the ferrophosphorus compound is selected from one or more of Fe3P, Fe2P, FeP, and FeP2.

[0011] The present invention uses ferrophosphorus compounds as raw materials to avoid the introduction of NO3 - 、SO4 2- , Cl - , thus avoiding NO x 、SO x It can prevent the emission of toxic and harmful gases such as Cl2, and is safe and environmentally friendly.

[0012] Preferably, in S1, the ball mill is a high-energy ball mill, the rotation speed of the ball mill is 500-800 r / min; the ball milling time is 5-10 h, and the ball-to-material ratio is 2-5:1.

[0013] Preferably, in S1, the sizes of the zirconium balls for ball milling include Φ3 mm, Φ10 mm and Φ20 mm, and the mass ratio of Φ3 mm, Φ10 mm and Φ20 mm is (30-40):(30-40):(25-30).

[0014] Controlling the ball milling conditions helps to mix the material system evenly while reducing and controlling the particle size distribution of the slurry.

[0015] Preferably, in S1, the particle size D50 after ball milling is 1-5 μm.

[0016] The ball milling process breaks larger particles into smaller ones, thereby reducing the difference in particle size, making the particle distribution more uniform, and enhancing the reactivity of the particles. However, excessive ball milling will cause excessive particle refinement, resulting in agglomeration and affecting the uniformity of distribution.

[0017] Preferably, in S1, the calcination comprises introducing a reaction gas and calcining at 700-900° C. for 10-15 hours.

[0018] Controlling the calcination conditions helps the reaction proceed fully. When the calcination temperature is too low, it is difficult to generate a pure phase of ferrous phosphate precursor due to incomplete reaction. When the reaction temperature is too high, it will cause excessive grain growth and affect the electrical properties of the product.

[0019] More preferably, the reaction gas is selected from one or more of CO2 and O2.

[0020] Preferably, in the S1, the intermediate phase is Fe3(PO4)2.

[0021] Preferably, in the S2, the pyrophosphate is selected from one or more of Na4P2O7 and Na2H2P2O7.

[0022] Preferably, in said S2, the molar ratio of the intermediate phase to the pyrophosphate is 1:(1-1.015).

[0023] The molar ratio of the intermediate phase to pyrophosphate within a certain range helps to reduce the probability of formation of the inert phase sodium iron phosphate and improve the purity and electrical properties of the composite sodium iron phosphate.

[0024] Preferably, in S2, the carbon source is selected from one or more of glucose, sucrose, starch, citric acid, polyvinyl alcohol, polyethylene glycol, carbon black, carbon nanotubes, graphite, and graphene.

[0025] While participating in the redox reaction, the carbon source is partially coated on the surface of the material to build a conductive network and improve the conductive properties of the material.

[0026] Preferably, in S2, the mass of the carbon source is 5-15% of the mass of the sodium ion positive electrode material.

[0027] Preferably, in S2, the solvent is selected from one or more of methanol, ethanol, glycerol and isopropanol.

[0028] When choosing a solvent, factors such as its compatibility with reactants and products, solubility, polarity, toxicity, and environmental friendliness should be considered.

[0029] Preferably, in S2, the mass ratio of the sum of the mass of the mesophase and the pyrophosphate to the mass of the solvent is (30-50):(40-70).

[0030] Preferably, in said S2, the drying temperature is 60-90°C.

[0031] Preferably, in said S2, the sintering comprises first sintering at 100-200°C under nitrogen protection for 1-3 hours; and then sintering at 550-650°C under nitrogen protection for 8-10 hours.

[0032] During the sintering process, parameters such as sintering temperature, sintering time and atmosphere need to be strictly controlled to ensure the purity of the material's phase composition, the crystallinity of the crystal structure and excellent electrochemical properties.

[0033] Preferably, in S2, the mesh size after crushing is 100-500 meshes.

[0034] The present invention also provides a sodium ion positive electrode material prepared by the above preparation method.

[0035] An application of the above-mentioned sodium ion positive electrode material or the sodium ion positive electrode material prepared by the above-mentioned preparation method in a sodium ion battery.

[0036] The beneficial effects of the present invention are:

[0037] (1) The present invention provides a method for preparing a composite sodium iron phosphate positive electrode material. The process uses a phosphorus iron compound as a raw material, synthesizes Fe3(PO4)2 in the first step, and then mixes and sinters it with Na4P2O7 to prepare Na4Fe3(PO4)2P2O7, which has extremely high atomic economy;

[0038] (2) The present invention overcomes the problem of local enrichment of water-insoluble iron sources, which leads to the generation of inert sodium ferric phosphate of iodine type when the local iron content is high. The product formula of the method of the present invention is easy to control, the synthesized product has high purity and excellent electrochemical properties, and is more suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram of the process for preparing the sodium ion positive electrode material proposed in the present invention.

[0040] Figure 2 The XRD diagrams of ferrophosphide compounds and Fe3(PO4)2 prepared under different conditions in Examples 1-3.

[0041] Figure 3This is the XRD pattern of the sodium ion positive electrode material prepared in Example 2.

[0042] Figure 4 This is the SEM image of the sodium ion positive electrode material prepared in Example 2. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is described in detail through specific embodiments.

[0044] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.

[0045] High energy ball mill: Pulverisette 5 from FRITSCH, Germany.

[0046] Example 1

[0047] A method for preparing a sodium ion positive electrode material comprises the following steps:

[0048] S1. Preparation of Fe3(PO4)2: According to the atomic stoichiometric ratio of Fe3P2, 10 mol Fe2P and 10 mol FeP were weighed to obtain a mixture. The mixture and zirconium balls of different sizes (the mass ratio of Φ3mm, Φ10mm and Φ20mm is 35:35:30) were loaded into a zirconia lined grinding jar at a ball-to-material ratio of 3:1. The mixture was run at 600 r / min in a high-energy ball mill. When the particle size test showed D50 = 1.5 μm, the ball milling was stopped. The product was transferred to a carbon dioxide atmosphere furnace, heated to 900°C at a heating rate of 3°C / min, maintained at a constant temperature for 10 hours, and then cooled to room temperature with the furnace to obtain a Fe3(PO4)2 intermediate phase.

[0049] Preparation of S2 and Na4Fe3(PO4)2P2O7 / C: first disperse the Fe3(PO4)2 intermediate phase and Na4P2O7 in an ethanol solution at a molar ratio of 1:1, and control the solid content at 40%. Then, add 1% of graphene by mass of sodium ferric pyrophosphate, 8% of glucose and 3% of citric acid to obtain a mixed solution. Ball-mill the mixed solution at a speed of 600 r / min to a particle size of D50=0.45 μm. After ball milling, the sample is dried in a vacuum drying oven at 80°C to obtain a dry solid powder material. The solid product is sieved through a 100-mesh sieve, pre-sintered at 150°C for 2h under an argon protective atmosphere, and then heated to 550°C, kept warm for 10h and naturally cooled. The solid product is sieved through a 200-mesh sieve to obtain Na4Fe3(PO4)2P2O7 / C positive electrode material.

[0050] Example 2

[0051] A method for preparing a sodium ion positive electrode material comprises the following steps:

[0052] S1. Preparation of Fe3(PO4)2: According to the atomic stoichiometric ratio of Fe3P2, 10 mol Fe2P and 10 mol FeP were weighed to obtain a mixture. The mixture and zirconium balls of different sizes (the mass ratio of Φ3mm, Φ10mm and Φ20mm is 35:35:30) were loaded into a zirconia lined grinding jar at a ball-to-material ratio of 3:1. The mixture was run at 600 r / min in a high-energy ball mill. When the particle size test showed D50 = 1.5 μm, the ball milling was stopped. The product was transferred to a carbon dioxide atmosphere furnace, heated to 800°C at a heating rate of 3°C / min, maintained at a constant temperature for 10 hours, and then cooled to room temperature with the furnace to obtain a Fe3(PO4)2 intermediate phase.

[0053] S2 and Na4Fe3(PO4)2P2O7 / C were prepared as in Example 1.

[0054] Example 3

[0055] A method for preparing a sodium ion positive electrode material comprises the following steps:

[0056] S1. Preparation of Fe3(PO4)2: According to the atomic stoichiometric ratio of Fe3P2, 10 mol of Fe2P and 10 mol of FeP were weighed to obtain a mixture. The mixture and zirconium balls of different sizes (the mass ratio of Φ3mm, Φ10mm and Φ20mm is 35:35:30) were loaded into a zirconia lined grinding jar at a ball-to-material ratio of 3:1. The mixture was run at 600 r / min in a high-energy ball mill. When the particle size test showed that D50 was 1.5 μm, the ball milling was stopped. The product was transferred to a carbon dioxide atmosphere furnace, heated to 700°C at a heating rate of 3°C / min, maintained at a constant temperature for 10 hours, and then cooled to room temperature with the furnace to obtain a Fe3(PO4)2 intermediate phase.

[0057] S2, Na4Fe3(PO4)2P2O7 / C were prepared as in Example 1

[0058] Example 4

[0059] A method for preparing a sodium ion positive electrode material comprises the following steps:

[0060] S1. Preparation of Fe3(PO4)2: According to the atomic stoichiometric ratio of Fe3P2, 10 mol Fe3P, 10 mol Fe2P and 10 mol FeP were weighed to obtain a mixture. The mixture and zirconium balls of different sizes (the mass ratio of Φ3mm, Φ10mm and Φ20mm is 35:35:30) were loaded into a zirconia lined grinding jar at a ball-to-material ratio of 3:1. The mixture was run at 600 r / min in a high-energy ball mill. When the particle size test showed D50 = 1.5 μm, the ball milling was stopped. The product was transferred to a carbon dioxide atmosphere furnace, heated to 800°C at a heating rate of 3°C / min, maintained at a constant temperature for 10 hours, and then cooled to room temperature with the furnace to obtain a Fe3(PO4)2 intermediate phase.

[0061] S2 and Na4Fe3(PO4)2P2O7 / C were prepared as in Example 1.

[0062] Comparative Example 1

[0063] The only difference between Comparative Example 1 and Example 1 is that the mixed material in S1 is insoluble ferric phosphate, and the other steps are the same as those in Example 1.

[0064] The positive electrode material prepared above, the conductive carbon black, and the binder PVDF were weighed in a mass ratio of 8:1:1 and poured into a mortar. After being fully ground, they were placed in a small beaker, and then an appropriate amount of NMP was added for 12 hours of magnetic stirring. The slurry was coated on aluminum foil with a slurry coater and placed in a vacuum drying oven at 100°C for 12 hours. After being taken out and dried, the aluminum foil was cut into a circular electrode with a diameter of 12 mm using a manual slicer, i.e., the positive electrode.

[0065] The button half-cell uses the CR2025 battery case produced by Kojing Zhida Technology Co., Ltd., and is assembled in the order of positive electrode shell-positive electrode sheet-65μl corresponding electrolyte-glass fiber separator-65μl corresponding electrolyte-sodium metal negative electrode-circular nickel mesh with a diameter of 14mm-negative electrode shell. The cells are stacked neatly with the center of the circle as the axis, and finally sealed with an electric button battery sealing machine.

[0066] The performance of the sodium ion batteries in the embodiments and comparative examples was tested, and the test results are shown in Table 1.

[0067] Table 1

[0068]

[0069]

[0070] From the comparison of the data results of the embodiment and comparative example 1 in Table 1, it can be seen that the first discharge specific capacity and the capacity retention rate of 200 cycles at 0.2C of Na4Fe3(PO4)2P2O7 / C prepared by the present invention based on the uniform Fe3(PO4)2 intermediate phase are higher than those of the sodium iron phosphate pyrophosphate positive electrode material prepared with commercial iron phosphate as the iron source. Compared with embodiments 2 and 4, the electrical performance of embodiment 1 decreases slightly with the increase of temperature because the Fe3(PO4)2 particles grow at high temperature; in addition, the Fe3(PO4)2 intermediate phase is impure in embodiment 3 due to the low calcination temperature, which also leads to the subsequent decrease of electrical performance.

[0071] Figure 1 The schematic diagram of the process for preparing the sodium ion positive electrode material proposed in the present invention. In the preparation method of the present invention, it is mainly based on the chemical reaction equations 2Fe3P2+16CO2→2Fe3(PO4)2+16CO and Fe3(PO4)2+Na4P2O7+C→Na4Fe3(PO4)2P2O7 / C, by first using phosphide and carbon dioxide as raw materials to synthesize Fe3(PO4)2 intermediate phase, and then combining sodium pyrophosphate and carbon source to synthesize sodium iron phosphate pyrophosphate composite material.

[0072] During the preparation of sodium iron phosphate pyrophosphate, when the local iron content is high, inert sodium iron phosphate ore type sodium iron phosphate will be generated, which will have an adverse effect on its electrochemical performance. In the prior art, the direct sintering method is adopted. Since it is difficult to completely and evenly mix a variety of sintering raw materials, it is difficult to avoid local enrichment of iron elements, resulting in the obtained sodium iron phosphate pyrophosphate often being doped with inert phases. In the preparation method provided by the present invention, high-purity sodium iron phosphate pyrophosphate is synthesized through precise raw material ratios and strictly controlled process conditions. The composite sodium iron phosphate pyrophosphate polyanion-type positive electrode material obtained by the preparation process of the present invention exhibits excellent comprehensive electrochemical properties and is suitable for sodium ion batteries.

[0073] Figure 2 The XRD patterns of the ferrophosphorus compound and Fe3(PO4)2 prepared under different conditions in Examples 1-3 are shown. In order to synthesize a uniform Fe3(PO4)2 intermediate phase, the Fe-P raw material and the sintering process were regulated. Figure 2 From the XRD comparison diagram, we can see that when the temperature is 700°C, some ferrophosphide compounds are not completely reacted, and when the temperature is higher than 800°C, a pure Fe3(PO4)2 intermediate phase is obtained.

[0074] Figure 3 This is the XRD diagram of the Na4Fe3(PO4)2P2O7 / C positive electrode material prepared in Example 2.

[0075] Figure 4The microscopic morphology and particle size of the Na4Fe3(PO4)2P2O7 / C positive electrode material prepared in Example 2 were characterized by scanning electron microscopy. The primary particles were mixed and agglomerated, the particle size of small particles was about 200nm, and the size of large particles was 1μm. At the same time, filamentous carbon coating was observed surrounding the positive electrode material.

[0076] In summary, the sodium ion positive electrode material provided by the present invention has high purity, and the sodium ion battery has excellent capacity retention. The method for preparing the sodium ion positive electrode material of the present invention helps to inhibit the enrichment of iron elements, reduce the local iron-phosphorus ratio, and inhibit the formation of the electrochemically inert phase sodium iron phosphate; while having extremely high atomic economy, it solves the environmental protection, safety, cost and other problems existing in the preparation of sodium ion battery positive electrode material sodium iron phosphate pyrophosphate.

[0077] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a sodium ion positive electrode material, characterized in that: The following steps are involved: S1, calcining the ferrophosphorus compound after ball milling to obtain an intermediate phase; S2. The intermediate phase is mixed with pyrophosphate, a carbon source, and a solvent, dried, sintered, and crushed to obtain a sodium ion positive electrode material, namely, a sodium iron phosphate pyrophosphate composite material.

2. The preparation method according to claim 1, characterized in that: In the S1, the ferrophosphorus compound is selected from one or more of Fe3P, Fe2P, FeP, and FeP2.

3. The preparation method according to claim 1, characterized in that: In the S1, the ball mill is a high-energy ball mill, the rotation speed of the ball mill is 500-800r / min; the ball milling time is 5-10h, and the ball-to-material ratio is 2-5:

1.

4. The preparation method according to claim 1, characterized in that: In the S1, the particle size D50 after ball milling is 1-5 μm.

5. The preparation method according to claim 1, characterized in that: In the S1, the calcination includes introducing a reaction gas and calcining at 700-900°C for 10-15h; the reaction gas is selected from one or more of CO2 and O2.

6. The preparation method according to claim 1, characterized in that: In the S2, the pyrophosphate is selected from one or more of Na4P2O7 and Na2H2P2O7; the carbon source is selected from one or more of glucose, sucrose, starch, citric acid, polyvinyl alcohol, polyethylene glycol, carbon black, carbon nanotubes, graphite, and graphene.

7. The preparation method according to claim 1, characterized in that: In the S2, the solvent is selected from one or more of methanol, ethanol, glycerol, and isopropanol.

8. The preparation method according to claim 1, characterized in that: In the S2, the sintering includes first sintering at 100-200°C under nitrogen protection for 1-3 hours; and then sintering at 550-650°C under nitrogen protection for 8-10 hours.

9. A sodium ion positive electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the sodium ion positive electrode material according to claim 9 or the sodium ion positive electrode material prepared by the preparation method according to any one of claims 1 to 8 in a sodium ion battery.

Citation Information

Patent Citations

  • Method for preparing FexPO4-containing substances from ferrophosphorus at low temperature

    CN106006597A

  • Method of preparing ferrous phosphate

    CN107161972A

  • Method for preparing composite sodium ferric phosphate positive electrode material by using iron slag solid waste

    CN117246987A

  • Preparation method of sodium ferric pyrophosphate composite material

    CN118458724A